Ice abrasion testing of high performance concrete for offshore structures - Shamsutdinova, Guzel; Hendriks, Max; Fosså, Kjell Tore; Jacobsen, Stefan (The Nordic Concrete Federation Oslo, 2019)
Offshore concrete structures exposed to drifting sea ice have abrasion of the concrete surface caused by the mechanical contact between ice and concrete in the order of 0.1 to 1 mm per year. The concrete-ice abrasion laboratory at NTNU, and results of our recent research of the laboratory simulation of concrete-ice abrasion, showed average abrasion depths of 0.01–0.35 mm for high-performance concrete after 3 kilometres of sliding ice, a severe-mild wear-transition, that abrasion is related to cutting of peaks, formation of valleys, aggregate protrusion by wear of ITZ. The strength – abrasion relation proposed by Huovinen was less clear due to the severe-mild transition. Key words: Concrete, ice, abrasion, ITZ, surface topography. publishedVersion